Solubility of vesicular stomatitis virus M protein in the cytosol of infected cells or isolated from virions. - McCreedy, B J (1990)
The peripheral membrane M protein of vesicular stomatitis virus purified by detergent extraction of virions and ion-exchange chromatography was determined to be a monomer in the absence of detergent at high salt concentrations. Reduction of the ionic strength below 0.2 M resulted in a rapid aggregation of M protein. This self-association was reversible by the detergent Triton X-100 even in low salt. However, aggregation was not reversible by high salt concentration alone. M protein is initially synthesized as a soluble protein in the cytosol of infected cells, thus raising the question of how the solubility of M protein is maintained at physiological ionic strength. Addition of radiolabeled M protein purified from virions to unlabeled cytosol from either infected or uninfected cells inhibited the self-association reaction. Cytosolic fractions from infected or uninfected cells were equally effective at preventing the self-association of M protein. Self-association could also be prevented by an irrelevant protein such as bovine serum albumin. Sedimentation velocity analysis indicated that most of the newly synthesized M protein is monomeric, suggesting that the solubility of M protein in the cytosol is maintained by either low-affinity interaction with macromolecules in the cytosol or interaction of a small population of M-protein molecules with cytosolic components.